ANALYSIS OF GLYCEMIC BEHAVIOR IN ADULT RATS WHEN SUBMITTED TO THE DIETS WITH DIFFERENT CONCENTRATIONS OF CARBOHYDRATES AND TRAINING OF SWIMMING (Fiep Bulletin - online, 2015)
This study aims to verify the relations between consumption of simple carbohydrate in the diet and glycemic behavior in Wistar rats submitted to the swimming procedure.  The sample was composed of 32 rats of the Wistar ancestry weighing between 200 and 300 g in the beginning of the experiment, being 20 animals for the experimental group that was exercised and 12 animals for the group control that was kept sedentary, of these there was an exercised group and a sedentary one with hyperglycidic diet, and an exercised group and a sedentary group with normal diet. The hyperglycidic diet consisted of an addition of 5% of sucrose in the water ingested for the animals. The used physical training was the swimming procedure that was carried through five times per week with duration of one hour.  In relation to the dependent 0 variable amount of consumed ration/day, observed effect of the physical exercise and the diet in the biggest consumption for the trained or sedentary rats without diet, when compared with the trained or sedentary animals with diet. It was observed, also, a high water consumption carbohydrate for the rats with diet, as well as a significant reduction of the carbohydrate/day consumption. In the same way there was a difference significant statistics in relation to the carbohydrate/day consumption between the groups in relation to the independent variable diet so that the sedentary rats had had greater consumption of sucrose in relation to the trained ones. The variance analysis shows that there was no significant difference in the glycemia of the groups, but showed to a trend the significance (p = 0,055979) with regard to the independent variable diet (animal with hiperglycidic diet x animal without hiperglycidic diet).  Or either, the rats that had received the diet hiperglycidic, sedentary or trained, had shown glycemia higher than those that had not received the diet.
Keywords: Physical exercise; Hiperglycidic Diet and glicemic behavior.